An Anticorruption Strategy for Revenue Administration - Das-Gupta, Arindam (World Bank, Washington, DC, 2012)
The World Bank defines corruption as the abuse of public office for private gain. Corrupt actions include the unilateral theft of public property by its steward and multi-party transactions in which beneficiaries bribe officials. Corruption can exist at all levels of public administration--from the highest officeholder to the lowest functionary. Because tax and customs administration often figure among the corrupt government agencies in developing countries, Bank projects that reform these administrations should include anti-corruption efforts. Any strategy to combat corruption must limit the motives and opportunities for public officeholders to abuse their positions. This should be done directly for unilateral corruption, while for multi-party corruption it can also be done indirectly by focusing on the supply side of bribes. Although we do not know enough to identify optimal anti-corruption strategies for different country situations, there is no one-size-fits-all strategy. Various elements from the menu of possibilities must be integrated into a coherent package. The Bank's approach in this area, outlined in this report, is in broad agreement with that of the International Monetary Fund. This report examines the motives and opportunities for corruption, and discusses incorporating strategies in reform projects, current country approaches, and lessons learned from experience.